Application of Density and Viscometric Techniques in Estimation of Aggregation Behaviour of Polyethylene Oxide with Impact of Molecular Mass of the Polymer - Rauf, Abdur; Kaleem Baloch, Musa; Rauf, Salma; Amanullah, Malik; Rehman, Wajid; Adeel, Muhammad; Akram, Mohammad (Asian Journal of Chemistry, 2013)
Polyethylene oxide having different molecular mass (35, 6, 2 Kg/mol) were studied by densitometry and viscometry in the temperature range of 20-50 ºC. Intrinsic viscosity (h) and interparticle interaction parameter (KH) were determined at various temperatures from viscometry. Micellar partial specific volume (nmic) and micellar density (rmic) were determined by density measurement at various temperatures. Energy of activation (Ea) was also calculated from intrinsic viscosity by using Arhenius equation. From the densitometric and viscometric results the amount of water in gram per gram associated with the aggregates of polymer (Wh) and shape factor of aggregate (micelle) were also determined. It was concluded that the intrinsic viscosity, micellar density and water associated with the polymer molecules were decreased as the temperature increased. While partial specific volume of polymer increased with the temperature.